Spectrophotometric determination amikacin in reaction with 1,2-naphthoquinone-4-sulfonic acid sodium salt - Portna, K. P.; Vasyuk, S.O.; Korzhova, A. S.; Портна, Катерина Павлівна; Васюк, Світлана Олександрівна; Коржова, Алла Станіславівна (Namakkal: Darshan Publishers, 2015)
A new spectrophotometric method for the quantitative determination of amikacinin pharmaceutical formulations has been developed. This method is based on the measurement of aqueous amikacin solutions absorption at 530 nm. The proposed method is actual according to the validation requirements of Ukrainian Pharmacopeia. The analytical method was optimized and validated by establishing the linearity (the correlation coefficient r = 1,000), precision and the accuracy. According to the experimental data, the technique can be correctly reproduced and it is suitable for using in laboratories of the State Inspection for Quality Control of Medicines and QCD of the chemicopharmaceutical enterprises.
Keywords: amikacin; quantitative determination; spectrophotometric method; drug dosage forms